(untitled) (Revista Logos Ciencia & Tecnología, 2019)
This article analyzes the school experience of an offending adolescent taking into account François Dubet and Danilo Martuccelli’s theory of sociology of the social and school experience. The general objective of this research is to understand how offending adolescents shape their school experience. The methodological approach is qualitative, using an in-depth interview and the review of documents. As a result, the school experience associated with failure and the relationship with the beginning of the consumption and sale of psychoactive substances is highlighted. It is concluded that the school experience of this offending adolescent contains school alienation in the form of a sense of loss of studies, in turn, placing stress on family relationships, integration with peer groups and the rupture of academic achievements in terms of life project.